A new species of Lagis (Annelida: Polychaeta: Pectinariidae) from Korean waters - Choi, Hyun Ki; Jung, Tae Won; Yoon, Seong Myeong (Zootaxa, 2017)
A new pectinariid polychaete, Lagis plurihamus sp. nov., is reported from intertidal habitats in the southern and western coasts of Korea. Lagis plurihamus sp. nov. is clearly distinguished from its congeners by a combination of the following morphological features: the cephalic veil bears usually 10–15 cirri; two pairs of thoracic branchiae are present on the segments 3 and 4; the scaphe is robust with 9–14 delicate scaphal hooks; the scaphal anal flap has a dorsal anal cirrus and fringed margin. Previously described species of Lagis from East Asia, L. bocki (Hessle, 1917) and L. crenulatus Sun & Qiu 2012 together with the newly described species L. plurihamus sp. nov., all have both short, recurved notochaetae with bordered serrations and long, straight notochaetae with fine serrations. We provide detailed description and illustrations with SEM photographs for the new species. A revised key to all Lagis species is also provided with a comparison of the morphological characteristics of them.